2014
DOI: 10.1523/jneurosci.4013-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Longevity Manipulations Differentially Affect Serotonin/Dopamine Level and Behavioral Deterioration in AgingCaenorhabditis elegans

Abstract: Aging is accompanied with behavioral and cognitive decline. Changes in the neurotransmitter level are associated with the age-related behavioral deterioration, but whether well-known longevity manipulations affect the function of neurotransmitter system in aging animals is largely unclear. Here we report that serotonin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…While several methods extracting neurotransmitters from brain tissue are often laborious due to pretreatment or derivatization steps [13, 18, 35, 46], we developed a fast and simple extraction protocol allowing high-throughput analyses. In trying to adopt published tissue [11] and C. elegans extraction [34, 47] protocols, the stability of the isotopic labelled internal standards could only be insured using a new extraction medium containing 0.002 M sodium thiosulfate in 0.2 M PCA. The certain instability of the monitored neurotransmitter underlines the importance and advantage of the utilizing stable-isotopic labelled internal standards, as they allow for trustworthy correction of analyte loss when added directly to the extraction solvent.…”
Section: Discussionmentioning
confidence: 99%
“…While several methods extracting neurotransmitters from brain tissue are often laborious due to pretreatment or derivatization steps [13, 18, 35, 46], we developed a fast and simple extraction protocol allowing high-throughput analyses. In trying to adopt published tissue [11] and C. elegans extraction [34, 47] protocols, the stability of the isotopic labelled internal standards could only be insured using a new extraction medium containing 0.002 M sodium thiosulfate in 0.2 M PCA. The certain instability of the monitored neurotransmitter underlines the importance and advantage of the utilizing stable-isotopic labelled internal standards, as they allow for trustworthy correction of analyte loss when added directly to the extraction solvent.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by observed distributions of radiocarbon (carbon-14) and silicic acid (Si(OH) 4 ) in the ocean. For example, de Lavergne and colleagues report the presence of a 'shadow zone' of old, radiocarbon-depleted water in the northern Indian and Pacific oceans at depths of 1-2.5 km (see Fig.…”
Section: A Genetic Cause Of Age-related Declinementioning
confidence: 57%
“…Some of the authors of the current paper had previously demonstrated 4 that changes in expression of the enzyme BAS-1 correlate with age-related declines in two traits -mating virility and pumping of the pharynx, which brings food into the intestine from the environment. In the current study, the researchers mapped the genetic variants that modulate BAS-1 expression, and found polymorphisms in a single gene that were responsible for about half of the variation in age-related decline in these two traits between strains.…”
Section: A Genetic Cause Of Age-related Declinementioning
confidence: 75%
“…At least 20 animals per strain per assay were counted. , shl-1(ok1168), ncs-4(tm4409), ncs-5(tm4951), shl-1(ok1168);ncs-4(tm4409), and Triple KO mutant males was conducted as described previously (Yin et al, 2014) with some modifications. Briefly, 1 male of each strain together with two N2 hermaphrodites were placed on a 3.5 cm NGM plate seeded with 5-mm-diameter lawn (10 l of OP50 was spotted onto NGM plate, allowing to grow for ϳ1 day).…”
Section: Methodsmentioning
confidence: 99%
“…Since then, the components of K ϩ currents in muscle cells have been well documented. Three K ϩ channels, SHK-1, SHL-1, and SLO-2, were reported to constitute the macroscopic outward K ϩ currents in muscle cells (Yuan et al, 2000;Santi et al, 2003;Fawcett et al, 2006;Gao and Zhen, 2011;Liu et al, 2011). Under physiological conditions with low intracellular concentrations of Cl Ϫ (4 -10 mM) and Ca 2ϩ (10 -100 nM), K ϩ currents with typical fast transient outward components were elicited by a series of voltage steps applied from Ϫ80 to ϩ80 mV (in 20 mV increments) from a holding potential of Ϫ80 mV in cultured myocytes of N2 worms (Fig.…”
Section: Shl-1 Forms Functional Complex With Cekchips In Body Wall Mumentioning
confidence: 99%